Konflik Batin Tokoh Toba Dalam Naskah Drama Janji Putri Ikan Karya Russel Akbar Fauzi : Pendekatan Psikologi Sastra - Sartika, Meinar Donna; Nasution, Ikhwanuddin; Marsella, Emma (Universitas Labuhanbatu, 2024)
This research aims to 1) describe the factors that cause the main character's inner conflict, 2) describe the inner conflict experienced by the main character. This research uses a qualitative descriptive research method with a literary psychology approach. The data source in this research is the drama script Janji Putri Ikan by Russel Akbar Fauzi with a research focus on the inner conflict of the Toba character and the factors causing the conflict which are studied using a literary psychology approach that refers to Kurt Lewin's theory. The data collection technique used was an interview technique which was then analyzed using descriptive analysis. Finally, data analysis was carried out on the sentences in the drama text related to the issues raised. The results of the research show the following: The inner conflict experienced by the character Toba in the drama script, namely doubt, conflict, disappointment. Meanwhile, the factors causing conflict in the drama script Janji Putri Ikan by Russel Akbar Fauzi are a) differences between individuals, b) cultural differences, and 3) clashes of interests.